STUDI TOXOPLASMOSIS PADA PENDERITA SCHIZOPHRENIA DI RUMAH SAKIT JIWA PROVINSI NTB - Ersandhi Resnhaleksmana; Nursardjan Nursardjan; I Gusti Ayu Nyoman Danuyanti (poltekkes kemenkes mataram, 2014)
Abstract: Toxoplasmosis, a disease caused by Toxoplasma gondii, a parasite of humans and animals scattered throughout the world. Infection T. gondii into the body of most real place in the reticuloendothelial tissues and the brain with symptoms of central nervous system often leave residual symptoms, such as mental and motor retardation. This phenomenon often occurs in people with schizophrenia. This study aims to determine the toxoplasmosis in patients with schizophrenia in Rumah sakit jiwa Provinsi NTB. The Methods of This study used an observational analytic design with cross-sectional design to determine the percentage of toxoplasmosis, by examination of the ELISA for determination of IgG T. gondidi serum samples of patients with schizophrenia at Rumah Sakit Jiwa Provinsi NTB. The research was conducted in July-November 2011, with a total sample size is 42 people. The idependent variabel is Toxoplasmosis and the dependent variabel is patient with schizophrenia.There is a percentage of toxoplasmosis in patients with schizophrenia was 54.8% (23 people) with higher levels of IgG T. gondii highest was 300 UI / ml. From the results of this study indicate the presence of infection T. gondii in patients with schizophrenia at Rumah Sakit jiwa Provinsi NTB.